Comparison of Cases with Anterior Cruciate Ligament Reconstruction Accompanied by Simultaneous Medial Meniscus Bucket Handle Tear Repair and Isolated Medial Meniscus Bucket Handle Tear Repair - Akalın, Yavuz; Avcı, Özgür; İnce, Savaş İ.; Çevik, Nazan; Şahin, İsmail G.; Öztürk, Alpaslan (The Journal of Knee Surgery, 2021)
The aim of this study was to evaluate the success of the all-inside repair technique for medial bucket-handle meniscus tear (BHMT) and the factors affecting healing. A total of 36 patients with BHMT who were operated between 2012 and 2018 and completed final follow-up examinations were included in the study. Functional evaluation was made with the International Knee Documentation Committee (IKDC) score, Lysholm score, and Tegner score. Healing was evaluated on magnetic resonance imaging (MRI) slices. The patients were evaluated with respect to the effect on healing of factors such as demographic data, body mass index (BMI), smoking status, anterior cruciate ligament tear reconstruction (ACLTR) applied at the same time as BHMT repair, and the tear being chronic or acute. The mean age of the patients was 28.6 ± 8.6 years (range,18–46 years), the mean follow-up period was 25.8 ± 13.9 months (range, 13–59 months), and BMI was mean 25.6 ± 3.5 kg/m2 (range, 20.1–30.5 kg/m2). The meniscus tears were acute in 16 (44.4%) patients and chronic in 20 (55.6%). ACLTR was applied together with BHMT repair in 25 patients. The hybrid technique, as the outside-in technique in addition to the all-inside technique, was applied to 12 (33.3%) patients, where there was seen to be extension to the anterior horn. The failure rate was determined as 27.8% according to the postoperative MRI evaluation and the Barrett criteria. No positive or negative statistically significant effect on healing was determined of chronic BHMT or of simultaneous application of ACLTR (p = 1.00 and 0.457, respectively). Cigarette smoking and high BMI were determined to have a statistically significant negative effect on healing (p = 0.026 and 0.007, respectively). In conclusion, it can be seen that the success of the all-inside technique for BHMT remains controversial. Due to the features of the application, it can be used in meniscus tears of the posterior horn only. In the current study, with the success rate of 72.2% of the all-inside technique in meniscus body tears, it was seen that a high success rate could not be achieved.
Keywords: bucket handle; meniscus; all inside; knee; cruciate ligament